Records of species of the snake eels genus \(Ophichthus\) (Family Ophichthidae) from Vietnam - Vo, Van Quang; Ho, Huans-Ching; Hibino, Yusuke; Le, Thao Thu Thi; Tran, Hoa Hong Thi; Tran, Thinh Cong (Vietnam Journal of Marine Science and Technology, 2024)
In Vietnam, the Ophichthus snake eel genus comprises 14 distinct species. This research aims to document and visually represent three previously undocumented findings and a newly discovered species. The species Ophichthus bicolor and Ophichthus machidai are meticulously described here, their characteristics based on five specimens each, gathered at depths of approximately 100–180 m and 50–100 m, respectively, in the vicinity of Quy Nhon. Additionally, Ophichthus obtusus is comprehensively described using 12 specimens collected from depths ranging from roughly 50 m to 120 m in the Quy Nhon and Nha Trang areas. Two specimens of Ophichthus shaoi were also recovered from Quy Nhon, contributing additional data regarding this species from Vietnamese waters. The identification of most species relied on careful examination of their morphological characters. These findings collectively raised the Ophichthus genus’s representation in Vietnamese waters by introducing three previously undocumented species, raising the total count to 17 compared to prior research. Furthermore, this study provides a comprehensive key to aid in identifying the various Ophichthus species found in Vietnam.